Diagnosis of a compacted area for mining through the mechanical resistance to the penetration using geostatistical methods in the Amazon Forest - Ribeiro, A. Í; Filho, A. J T; Longo, R. M. [UNESP]; De Melo, W. J. [UNESP]; Maciel, A. J S (My University, 2004)
The mining process promotes land modification and complete landscape alteration. Those alterations in the surface are shown more obviously in the aesthetical aspect as the visual elements of form, texture, climbs, complexity and color which composes the landscape. As a consequence, mining has impacts on the topography, in the soil, in the vegetation and in the area's drainage, with a direct influence on the enterprise. A quite common problem in the recovery of degraded areas in mineral exploration is the compaction of the soil due to the intense traffic of machines and earth movement. The most common problem of the compaction of a degraded surface is an increase of the mechanical resistance to the penetration of plant roots, a reduction of the aeration, an alteration of the flow of water and heat, also in the availability of water and nutrients. Thus, the present work had the basic objective of diagnosing the compaction of an area degraded by mining in a spacial way, through the mechanical resistance and the penetration, to guide the future subsoiling in the area requiring recovery. Through the studies, it was concluded that the krigagem method in agreement with the space variation allows the division of the area under study into sub areas facilitating a future work to reduce costs and unnecessary interference to the atmosphere. The method was shown to be quite appropriate and it can be used in the diagnosis of compaction in a degraded area by mining, foreseeing the subsoiling requirement.
Keywords: Ground vehicles; Mathematical models; Plants (botany); Soils; Traffic control; Water; Water aeration; Geostatistics; Mechanical resistance; Mineralogical properties; Semivariograma anisotropy; Mining